UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) KELAS IV SDN 04 MAMBEN DAYA - Muhammad Hafizin; Niswatul Hasanah; Lia Apriani (JURNAL ASIMILASI PENDIDIKAN, 2024)
This research aims to determine the improvement in Mathematics learning outcomes through the application of the TGT (Teams Games Tournament) learning model in class IV students at SD Negeri 4 Mamben Daya. This type of research is Classroom Action Research. The research subjects were fourth grade students at SD Negeri 4 Mamben Daya. The data analysis techniques used are observation techniques and data collection techniques. The results of this research show that the results of the evaluation using written tests in the form of essays to determine student learning outcomes are quite good, namely from pre-cycle, cycle I to cycle II there has been an increase. In the pre-cycle, an average score of 56.57 was obtained with a classical completeness of 32%, in the first cycle there was an increase, an average score of 66.5 was obtained with a classical completeness of 63%, so in the second cycle there was an increase with an average value of 79.8 with completeness classical of 89%. In this way, the implementation of the TGT (Teams Games Tournament) Learning Model can improve the Mathematics Learning Outcomes of Class IV Students at SD Negeri 4 Mamben Daya which can be seen from the number of students who have completed.